2005
DOI: 10.1162/0034653053327694
|View full text |Cite
|
Sign up to set email alerts
|

Generic Drug Industry Dynamics

Abstract: Because of its unique institutional and regulatory features, the generic drug industry provides a useful laboratory for understanding how competition evolves. We exploit these features to estimate a system of structural relationships in this industry, including the relationship between price and the number of competitors, and between drug characteristics and the entry process. Our methodology yields a number of findings regarding industry dynamics. We find that generic drug prices fall with increasing number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
150
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(157 citation statements)
references
References 17 publications
7
150
0
Order By: Relevance
“…They found that generic entry depended on expected profits. This finding has been supported in the subsequent literature: Frank and Salkever (1997) reported that the number of generic entrants depended positively on market size in terms of drug sales before the patent expiration; Bae (1997), using a duration model, found that generic drug entry was faster on average in larger markets; Scott Morton (1999Morton ( , 2000 found that brand-name product revenues affected generic entry positively; Reiffen and Ward (2005) concluded that there were more and faster entries in markets with larger expected profits and that the number of firms in each market segment depended on the expected market size; and Saha et al (2006) found that on average there were more entries in the largest markets in terms of sales. Bae (1997) also showed that entries were faster for drugs that mainly treat chronic diseases, and Scott Morton (1999Morton ( , 2000 found that this factor made entry more likely.…”
Section: The Spanish Pharmaceutical Marketmentioning
confidence: 72%
“…They found that generic entry depended on expected profits. This finding has been supported in the subsequent literature: Frank and Salkever (1997) reported that the number of generic entrants depended positively on market size in terms of drug sales before the patent expiration; Bae (1997), using a duration model, found that generic drug entry was faster on average in larger markets; Scott Morton (1999Morton ( , 2000 found that brand-name product revenues affected generic entry positively; Reiffen and Ward (2005) concluded that there were more and faster entries in markets with larger expected profits and that the number of firms in each market segment depended on the expected market size; and Saha et al (2006) found that on average there were more entries in the largest markets in terms of sales. Bae (1997) also showed that entries were faster for drugs that mainly treat chronic diseases, and Scott Morton (1999Morton ( , 2000 found that this factor made entry more likely.…”
Section: The Spanish Pharmaceutical Marketmentioning
confidence: 72%
“…Some studies, such as Reiffen and Ward (2005), argue that the generics industry provides an interesting area for empirical studies for analyzing the competitiveness of a market. Reasons for this include: i) each active ingredient can be considered as an experiment; ii) it is possible to observe the initial opening of the market by taking patent expiry into account; and iii) the companies will bear the relevant costs of requesting authority approval before knowing when and how many rivals will enter into the market (REIFFEN E WARD, 2005, p. 37).…”
Section: Databasementioning
confidence: 99%
“…First, it does not allow for it to be identified how characteristics of the Brazilian market (such as income, population size, epidemiological and sanitary conditions, and other characteristics described in Morton (1997) and Kyle (2006)) affect the pattern of entry of generic drugs into Brazil. For this, a dynamic entry model would need to be estimated using parametric and non-parametric methods, such as in Reiffen and Ward (2005). However, the database described and used in this article is not rich enough for such methods to be employed.…”
Section: Introductionmentioning
confidence: 99%
“…In 1994 Ranbaxy was enlisted on the Luxembourg stock exchange to accumulate financial support for its expansion in European market. Generic drug market in the European countries was more complex than US market because most of the countries in Europe had a policy of generic substitution and unique barriers to entry (Reiffen & Ward, 2005;Yeoh, 2011). To face these challenges Ranbaxy focused first into generic products segment, establishing strong foothold moved to selective (prescription) products.…”
Section: European Marketsmentioning
confidence: 99%